2023
DOI: 10.1111/ddg.15005
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the COVID‐19 pandemic on inpatient skin surgery in Germany: results of the DESSI‐survey

Galina Balakirski,
Silke C. Hofmann,
Nataliia Isselmann
et al.

Abstract: Background:The aim of the survey was to investigate a possible impairment of inpatient dermatological and dermatosurgical care in Germany due to the COVID-19 pandemic. Methods: An online survey on the impact of pandemic-related measures on inpatient care was sent to all German dermatology clinics. Only one person per clinic was asked to participate. Data analysis was mainly descriptive. Differences between university hospitals and non-university hospitals were calculated using the Chi-square test. Results: Fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 29 publications
0
3
0
1
Order By: Relevance
“…Existing literature suggests that melanoma overall staging and histological prognostic features have worsened since the beginning of the COVID-19 pandemic [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ]. For instance, a four-year Romanian study (2018–2022) that did not report the use of a prioritization system showed higher Breslow thickness and more stage-III patients during the pandemic [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Existing literature suggests that melanoma overall staging and histological prognostic features have worsened since the beginning of the COVID-19 pandemic [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ]. For instance, a four-year Romanian study (2018–2022) that did not report the use of a prioritization system showed higher Breslow thickness and more stage-III patients during the pandemic [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Fu et al, 2023, have also reported worse short-term survival for Ontario melanoma patients during the pandemic in 2020 [9]. Several international studies have also shown that patients have presented with higher-stage melanoma since the start of the pandemic [10][11][12][13][14]; however, there is a scarcity of studies assessing wait times to melanoma surgery during the COVID-19 pandemic. No studies to date have explored the impact of the COVID-19 pandemic on melanoma surgical management, wait times, and staging in Canada.…”
Section: Introductionmentioning
confidence: 99%
“…3 A recent study could show that inpatient care of dermatosurgical patients -with the exception of cases with very large, fast-growing, or painful tumors -was also significantly restricted during the pandemic. 4 The suspected increase in tumor thickness associated with a reduced early detection and treatment of epithelial tumors was recently illustrated for a German population. 5 Following micrographically controlled excision of larger epithelial skin tumors, the surgeon is confronted with large wound defects that require extensive reconstruction.…”
Section: Introductionmentioning
confidence: 99%
“…3 Eine aktuelle Untersuchung konnte zeigen, dass auch die stationäre Versorgung dermatochirurgischer Patienten -mit Ausnahme sehr großer, schnell wachsender oder schmerzhafter Tumoren -während der Pandemie deutlich eingeschränkt war. 4 Die mit der reduzierten Früherkennung und Versorgung epithe-This is an open access article under the terms of the Creative Commons Attribution-NonCommercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes.…”
unclassified